Students' perceptions of instructor appropriateness and humor homophily. Issue 3 (3rd July 2019) - West, Mckay Steven; Martin, Matthew M.
ABSTRACT: Instructors use humor in the classroom in numerous ways, including behaving stupidly, offering impersonations, manipulating their nonverbals, telling a story, joke, or pun, and using a costume or prop. How students decode their instructors' use of humor impacts their feelings about the course and their instructors. In this study, we investigated students' ( N = 306) perceptions of their humor homophily with their instructors, as well as their overall view of the appropriateness of the instructor's classroom communication. Humor homophily was positively related to instructor humorousness, students' affect for their instructor, and their likelihood of enrolling in another class with their instructor. We also found that the intensity of instructor humorousness' relationship with student affect decreased when students perceived their instructor as appropriate. However, the more students found their instructors to be humorous and reported humor homophily, the more appropriate students rated their instructors' communication.